The Origin of T Tauri X-Ray Emission: New Insights from the Chandra Orion Ultradeep Project - Preibisch, Thomas; Kim, Yong-Cheol; Favata, Fabio; Feigelson, Eric D; Flaccomio, Ettore; Getman, Konstantin; Micela, Giusi; Sciortino, Salvatore; Stassun, Keivan; Stelzer, Beate; Zinnecker, Hans (The Astrophysical journal. Supplement series, 2005)
The Chandra Orion Ultradeep Project (COUP) provides the most comprehensive data set ever acquired on the X-ray emission of pre-main-sequence stars. In this paper, we study the nearly 600 X-ray sources that can be reliably identified with optically well-characterized T Tauri stars (TTSs) in the Orion Nebula Cluster. With a detection limit of L sub(x, min) 6 10 super(27.3) ergs s super(-1) for lightly absorbed sources, we detect X-ray emission from more than 97% of the optically visible late-type (spectral types F-M) cluster stars. This proves that there is no "X-ray-quiet" population of late-type stars with suppressed magnetic activity. We use this exceptional optical, infrared, and X-ray data set to study the dependencies of the X-ray properties on other stellar parameters. All TTSs with known rotation periods lie in the saturated or supersaturated regime of the relation between activity and Rossby numbers seen for main-sequence (MS) stars, but the TTSs show a much larger scatter in X-ray activity than that seen for the MS stars. Strong near-linear relations between X-ray luminosities, bolometric luminosities, and mass are present. We also find that the fractional X-ray luminosity L sub(X)/Lbol 0.1-2 M sub( )range. The plasma temperatures determined from the X-ray spectra of the TTSs are much hotter than in MS stars but seem to follow a general solar-stellar correlation between plasma temperature and activity level. The scatter about the relations between X-ray activity and stellar parameters is larger than the expected effects of X-ray variability, uncertainties in the variables, and unresolved binaries. This large scatter seems to be related to the influence of accretion on the X-ray emission. While the X-ray activity of the nonaccreting TTSs is consistent with that of rapidly rotating MS stars, the accreting stars are less X-ray active (by a factor of 62-3 on average) and produce much less well-defined correlations than the nonaccretors. We discuss possible reasons for the suppression of X-ray emission by accretion and the implications of our findings on long-standing questions related to the origin of the X-ray emission from young stars, considering in particular the location of the X-ray-emitting structures and inferences for pre -main-sequence magnetic dynamos.